2001
DOI: 10.1097/00007435-200104000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Mobiluncus spp Among Women With and Without Bacterial Vaginosis as Detected by Polymerase Chain Reaction

Abstract: Mobiluncus is more common in healthy women than previously suspected, with M mulieris as the predominant species. The significant difference in the prevalence of M curtisii between women with bacterial vaginosis and uninfected women suggests that this species could be involved in the pathogenesis of bacterial vaginosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 18 publications
0
25
0
4
Order By: Relevance
“…In particular, the ability to detect G. vaginalis in 50 to 60% of women without BV (7) violates Koch's second postulate regarding specificity for disease (4). Many additional cultivated bacteria have been isolated from women with BV, including Mobiluncus species, Mycoplasma hominis, and a variety of anaerobic bacteria such as Prevotella and Porphyromonas species (16,21). The recent identification of several fastidious vaginal bacteria using sequence-based detection methods adds to the list of potential bacterial pathogens in BV (5,6,13,26), but uncertainty regarding their contribution to pathogenesis persists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the ability to detect G. vaginalis in 50 to 60% of women without BV (7) violates Koch's second postulate regarding specificity for disease (4). Many additional cultivated bacteria have been isolated from women with BV, including Mobiluncus species, Mycoplasma hominis, and a variety of anaerobic bacteria such as Prevotella and Porphyromonas species (16,21). The recent identification of several fastidious vaginal bacteria using sequence-based detection methods adds to the list of potential bacterial pathogens in BV (5,6,13,26), but uncertainty regarding their contribution to pathogenesis persists.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have used taxon-directed conventional PCR assays to describe the prevalences of various bacterial species in vaginal samples, and while this method is much more sensitive at detecting minority bacterial species than broad-range PCR, it is also not reliably quantitative (7,21). There are few published studies that have used targeted qPCR methods to describe levels of vaginal bacteria, but most such studies were cross-sectional (22,23,27,28); even fewer studies have examined how vaginal bacterial concentrations change with antibiotic therapy (2).…”
Section: Discussionmentioning
confidence: 99%
“…Only one species of anaerobe (Mobiluncus curtisii) has been reported to resist destruction by free-living amoebae (241). This obligate nonsporeforming anaerobic bacterium, causing vaginosis (218) and, more rarely, abcesseses (69) and bacteremia (91,109), persisted for up to 4 to 6 weeks under aerobic conditions as a result of its internalization in Acanthamoeaba (241). Like H. pylori, M. curtisii may multiply aerobically when cocultured with free-living amoebae, while it requires otherwise strict atmospheric conditions for in vitro culture.…”
Section: Other Microorganisms Shown In Vitro To Resistmentioning
confidence: 99%
“…In particular, it may be interesting in the future to determine whether the vagina is colonized with freeliving amoebae and whether such colonization may be associated with gynecological infections. The pathogenicity of M. curtisii, which is a commensal inhabitant of the vaginal flora and an established agent of vaginoses (218), might be due to a disequilibrium in the ratio of bacteria to amoebae.…”
Section: Other Microorganisms Shown In Vitro To Resistmentioning
confidence: 99%
“…There are data that Mobiluncus spp. have never been isolated in pure cultures, but only in mixed cultures with other anaerobes in vaginal samples predominantly from patients with BV or pelvic inflammatory disease, or from amniotic fluid; however, the data's clinical significance is as of yet unclear (4,9,29). An investigation in rhesus macaques revealed that most of the tested animals carried such microorganisms, especially M. curtisii, in their vaginal ecosystem, which were harbored together with Gardnerella-like bacteria (9,30).…”
Section: Resultsmentioning
confidence: 99%